Pembinaan Karakter dan Kepemimpinan Mahasiswa Muslim melalui Kegiatan Basic Training Majelis Taklim - Ellis, Rusnawati; Mahaly, Sawal; Kubangun, Nur Aida; Yandry, Hengki; Rumalean, Iwan; Kalean, Armin (Universitas Negeri Gorontalo, 2025)
In the era of increasing globalization, Muslim students face significant challenges in maintaining moral and spiritual integrity amid modernization. Therefore, character and leadership development based on Islamic values has become an essential need in higher education. This study aims to strengthen students’ Islamic character and leadership through the Basic Training activities of the Majelis Taklim in the Guidance and Counseling Study Program at the University of Pattimura. The method used was a descriptive approach consisting of three stages: preparation, implementation, and evaluation through pre-test and post-test involving 45 participants. The results show a significant improvement in understanding Islamic values, discipline, social responsibility, and Islamic leadership. The participants’ average scores increased from 63.5%–70.1% to 86.9%–89.2%, with the highest improvement (24.1%) in Islamic leadership. This program effectively fosters students with strong character, noble morality (akhlaq al-karimah), and Islamic leadership qualities